2016
DOI: 10.1063/1.4941379
|View full text |Cite
|
Sign up to set email alerts
|

Coarse-grained simulations of poly(propylene imine) dendrimers in solution

Abstract: The behavior of poly(propylene imine) (PPI) dendrimers in concentrated solutions has been investigated using molecular dynamics simulations containing up to a thousand PPI dendrimers of generation 4 or 5 in explicit water. To deal with large system sizes and time scales required to study the solutions over a wide range of dendrimer concentrations, a previously published coarse-grained model was applied.Simulation results on the radius of gyration, structure factor, intermolecular spacing, dendrimer interpenetr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 37 publications
(40 reference statements)
5
19
0
Order By: Relevance
“…Along with single dendrimers in dilute solutions [14,15,16,17,18,19,20,21,22,23], much attention is attracted nowadays to concentrated solutions and melts [24,25,26,27,28,29,30,31,32,33,34], where intermolecular interactions of dendrimer molecules are significant. It is expected that the tree-like molecular morphology of dendrimers would distinguish their behavior from that of conventional linear polymers.…”
Section: Introductionmentioning
confidence: 99%
“…Along with single dendrimers in dilute solutions [14,15,16,17,18,19,20,21,22,23], much attention is attracted nowadays to concentrated solutions and melts [24,25,26,27,28,29,30,31,32,33,34], where intermolecular interactions of dendrimer molecules are significant. It is expected that the tree-like molecular morphology of dendrimers would distinguish their behavior from that of conventional linear polymers.…”
Section: Introductionmentioning
confidence: 99%
“…[16,20,21] Dendrimer melts with other chemistry were simulated in Ref. [22,23] and the coarse-grained non-equilibrium MD simulations were used for studies of the shear viscosity of dendrimer melts [24,25] and of the rheological properties of dendrimer melts undergoing planar elongational flow. [26] None of these studies investigated the dynamical shear-stress relaxation modulus.…”
mentioning
confidence: 99%
“…Furthermore, the G 4 and G 5 PPI models provided a clear concentration-dependent molecular picture in simulations of up to 1430 dendrimers in water from dilute to melt conditions and compared well with experimental SANS data. 36 It demonstrated that even at high concentrations each dendrimer remains a distinct entity and that structure factors computed using the approximations and assumptions experimenters need to employ start to diverge at rather low concentrations from structure factors derived directly from the simulation data.…”
Section: Modelmentioning
confidence: 99%